Drilling process of composite laminates : a tool based analysis - L. M. P. Durão (2010)
The distinctive characteristics of carbon fibre reinforced plastics, like low weight or high specific strength, had broadened their use to new fields. In order to join different components by using bolts, rivets or screws, one of the machining operations needed in composite structures is drilling. Usually, it is accepted that drilling can be carried out using conventional tools and machinery with adaptations. However, this operation can lead to different kind of damages being delamination the most severe as it can reduce the mechanical strength. The main mechanism responsible for delamination occurrence is the indentation caused by the drill chisel edge. It is accepted that a drilling process that reduces the thrust force exerted by the drill chisel edge during machining can decrease the risk of delamination. In this work, two combinations of the drilling process are compared: tool material HSS, WC and PCD and geometry twist, Brad and step. The parameters considered for analysis include: thrust force, delamination extension open-hole strength and bearing strength. Statistical techniques are used in the evaluation. The work performed shows that a proper combination of the factors involved, like tool material, drill geometry or cutting parameters, can help to reduce the occurrence of delamination.